Diagnostic performance of time-of-flight PET/CT for evaluating nodal metastasis of the axilla in breast cancer. Issue 9 (September 2019) - Mori, Mio; Fujioka, Tomoyuki; Katsuta, Leona; Tsuchiya, Junichi; Kubota, Kazunori; Kasahara, Mai; Oda, Goshi; Nakagawa, Tsuyoshi; Onishi, Iichiroh; Tateishi, Ukihide
Abstract : Objective: The aim of this study was to evaluate the performance of preoperative axillary lymph node assessment in breast cancer using time-of-flight 18F-fluorodeoxyglucose PET/computed tomography (TOF [F-18]FDG-PET/CT). Methods: Eighty-two women with breast cancer (mean age, 59.3 years; range, 30–84 years) underwent TOF [F-18]FDG-PET/CT scanning before surgery between January 2016 and June 2018 at our hospital. Visual analysis of FDG uptake and the maximum standardized uptake value (SUVmax) of axillary lymph nodes were compared with the pathological diagnoses. Results: There were 77 patients with invasive breast carcinoma (mean invasive long diameter, 18.5 mm; range, 2–90 mm) and five patients with noninvasive carcinoma. Axillary lymph node metastases were histologically confirmed in 13 of 82 patients (15.9%). SUVmax showed an area under a receiver operating characteristic curve of 0.916, and the cut-off value of 1.1 was appropriate. By visual assessment, there were 11 true positives, 15 false positives, 54 true negatives and two false negatives; the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 85%, 78%, 42%, 96% and 79%, respectively. SUVmax showed values of 69%, 99%, 90%, 94% and 94%, respectively. Conclusions: The sensitivity of TOF [F-18]FDG-PET/CT was as high as 85% by visual analysis. SUVmax using TOF [F-18]FDG-PET/CT showed high diagnostic performance for N-staging in breast cancer patients, especially high negative predictive value. The specificity, positive predictive value and accuracy of SUVmax were higher than those of visual analysis.